2009
DOI: 10.1055/s-0029-1220688
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Growth Hormone Replacement Therapy on Plasma Brain Natriuretic Peptide Concentration, Cardiac Morphology and Function in Adults with Growth Hormone Deficiency

Abstract: Six months GH replacement therapy induced a significant decrease in plasma BNP levels despite the majority of patients having plasma BNP within the normal range at baseline. A borderline decrease in diastolic deceleration time was observed, the clinical significance of which is unclear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 21 publications
0
8
0
1
Order By: Relevance
“…High levels of NT-proBNP are observed in patients with severe GH deficiency and are corrected by GH therapy (13,34,35). However, in such conditions, the observed changes in these natriuretic peptides are not correlated with changes in cardiac structure or function (35,36,37), thus suggesting that effects of GH are here independent of cardiovascular alterations. Alternatively, indirect effects of GH through its effects on kidney filtration and fluid equilibrium may also be considered.…”
Section: Discussionmentioning
confidence: 99%
“…High levels of NT-proBNP are observed in patients with severe GH deficiency and are corrected by GH therapy (13,34,35). However, in such conditions, the observed changes in these natriuretic peptides are not correlated with changes in cardiac structure or function (35,36,37), thus suggesting that effects of GH are here independent of cardiovascular alterations. Alternatively, indirect effects of GH through its effects on kidney filtration and fluid equilibrium may also be considered.…”
Section: Discussionmentioning
confidence: 99%
“…Since 2003 additional studies have been published [20][21][22][23][24][25][26][27][28][29][30]. Although the GH replacement doses in these newer studies are lower and less variable, conflicting result have still been reported [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…Two patients had isolated GHD whereas the rest had insufficiencies in at least one of the other pituitary axes: Adrenal axis (n = 10, mean hydrocortisone dose 20 mg/day, range [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30], thyroid axis (n = 13, mean thyroxin dose 85 lg/day, range 50-150) and gonadal axis (n = 12, 5 females, 7 males). Two patients had been treated with GH during childhood for *3 years, and the treatment had been paused for 5 and 20 years before entering this study.…”
Section: Patientsmentioning
confidence: 99%
“…The height of children is rapidly becoming a social issue as there is an increase in the number of people who are concerned about their child's height. As a result, GH therapy is being indiscriminately used without adequate protection against side effects [38][39][40][41][42][43][44][45][46][47]. This study investigated the beneficial effect of using spirulina as a dietary supplement on skeletal growth and growth-related hormone levels in growing male rats.…”
Section: Introductionmentioning
confidence: 99%